Assessment of Food Vendor Personal Hygiene in Public Areas to Support Sustainable Health (SDG 3) : Ungaran District Study (International Forum of Researchers and Lecturers, 2025)
Food vendors in public areas play an important role in providing quick meals for the community. Poor personal hygiene among food vendors can be a source of cross-contamination and increase the risk of foodborne illnesses such as diarrhea, typhoid, and food poisoning. Therefore, it is essential to evaluate the personal hygiene practices of food vendors in public areas to identify potential risks to public health. This study aims to assess the level of personal hygiene among food vendors in public areas and to identify the influencing factors. A descriptive quantitative design with an observational approach was used. The sample consisted of 49 food vendors operating in various public areas in Ungaran city, selected through purposive sampling. Data were collected through direct observation using a WHO-standard checklist and brief structured interviews. The results showed that most vendors met basic personal hygiene standards, such as having no open wounds (91.8%) and wearing clean clothes (81.6%). However, only 61.2% of vendors washed their hands with soap before handling food, and only 44.9% used gloves. Furthermore, 36.7% still reused disposable utensils, and only 53.1% stored eating utensils in closed containers. The availability of sanitation facilities and knowledge of hygiene were significant factors influencing hygienic behavior. The level of personal hygiene among food vendors in public areas varied and did not fully meet health standards. Educational efforts, regular supervision, and the provision of supporting facilities are urgently needed to improve hygiene quality and food safety in public spaces.